Analisis Yuridis Perkawinan dibawah Umur di Kecamatan Paleleh dan Paleleh Berdasarkan Undang-Undang No 16 Tahun Tahun 2019 Tentang Perkawinan - Aldi D. Butudoka; Nur Mohamad Kasim; Dolot Alhasni Bakung (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
This thesis aims to determine the age limit for marriage as regulated in Law Number 16 of 2019. In this Law, the minimum age limit for marriage is set at 19 (nineteen) years for both men and women. Apart from that, this thesis also examines the factors that cause underage marriage in Paleleh and West Paleleh Districts. Underage marriages are marriages that do not meet the minimum age limit for marriage as regulated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. In Law Number 16 of 2019 article 7 it is stated that marriage is only permitted if the man and woman have reached the age of 19 (nineteen) years. In this research, the author used an empirical research method, namely by going directly into the field to obtain data related to underage marriage in Paleleh and West Paleleh Districts. This research uses a descriptive approach in analyzing the data obtained. Based on research results, the number of underage marriages in Paleleh and West Paleleh sub-districts is still relatively high. This is proven by the high percentage of underage marriages in Paleleh and West Paleleh Districts from year to year based on underage marriage dispensation data from the KUA in Paleleh District. Apart from that, based on research results, there are several factors that cause underage marriages in Paleleh and West Paleleh Districts, including the factor of accidental marriage (pregnancy out of wedlock), and the factor of low level of education.